Temporal point-by-point arbitrary waveform synthesis beyond tera sample per second - Yiran Guan; Guangying Wang; Yanyan Zhi; Jingxu Chen; Lingzhi Li; Jiejun Zhang; Jianping Yao (Nature Communications)
Abstract Arbitrary waveform synthesizers are indispensable in modern information technology, yet electronic counterparts are limited by the speed of analog-to-digital converters to hundreds of GSa/s. While photonic-assisted synthesizers offer potential to surpass this ceiling, scalability and reconfigurability remain challenges. Here, we propose a temporal point-by-point arbitrary waveform synthesizer beyond TSa/s, leveraging an optical temporal Vernier caliper in the photonic synthetic dimension. The system, combining a mode-locked laser and a fiber loop, controls the sampling rate of synthesized waveforms by exploiting a slight detuning between the pulse period and the round-trip delay of the fiber loop. The experiment demonstrates generated waveforms with ultra-high, tunable sampling rate up to 1 TSa/s, an order of magnitude higher than state-of-the-art electronic counterparts. Additionally, the system supports up to 10.4 kilo-points in memory depth. As application examples, the generation of communication waveforms for high-speed wireless communications and linearly chirped microwave waveforms for high-resolution multi-target detection is demonstrated.